Bibliometric Analysis of Teacher Self-Efficacy in Primary Education - Aulia Wulandari; Sukarno Sukarno; Matsuri Matsuri (STAI Hubbulwathan Duri, 2023)
Teacher self-efficacy is the ability to believe in controlling or mastering certain situations. The level of self-efficacy of elementary school teachers will affect their work. This study aims to uncover study trends related to primary school teacher self-efficacy over the last three decades by using bibliometric analysis. The Scopus database was used to collect articles that matched the criteria, eventually yielding 164 articles from 1994–2022. The results showed that